PENGARUH MASASE KAKI TERHADAP SENSASI PROTEKSI PADA KAKI PASIEN DIABETES MELITUS TIPE II DENGANDIABETIC PERIPHERAL NEUROPATHY - Dimas Pramananta Harmaya (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Diabetes mellitus can lead some chronic complications. One of the most common complication is Diabetic Peripheral Neuropathy (DPN), which attacks the nerves and result in the patient diabetes melitus loss protective sensation in their feet. One way to overcome this DPN by doing foot massage. This study aims to determine the effect of foot massage to the protective sensation in type 2 diabetic patient’s foot in North Denpasar Community Health Center I.This study used a nonequivalent control group design with sample size of 10 in the treatment group and 10 in the control group. The data obtained from the results of examination by using a 10-g monofilament homemade. The results of data analysis using the Mann-Whitney test showed that p value <? (p = 0.003; ? = 0.05), it means there is a significant effect of foot massage with protective sensation on diabetic patient’s foot in North Denpasar Community Health Center I. Based on this research, it is recommended for health care professional to suggest and practice foot massage to patients with type 2 diabetes melitus on a regular basis to cope diabetic peripheral neuropathy and maintain a good sensation on the feet.